1996
DOI: 10.1111/j.1749-6632.1996.tb52954.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Mucosal Protective Immunity to Pneumococcal Surface Protein A

Abstract: To date our studies demonstrate that PspA is a highly immunogenic molecule in mice and that it can elicit immunity to otherwise fatal infections following iv, ip, in, and it challenge. Although the molecule is serologically variable, it is sufficiently cross-reactive so that immunization with a single PspA can protect against strains of highly diverse serotypes. It is anticipated that a vaccine composed of a mixture of carefully chosen PspA molecules will be able to elicit protective immunity to virtually all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…The N-terminal portion of the choline-binding protein PspA has been predicted to have a coiled-coil structure reminiscent of the M proteins of group A streptococci (46), and this might be expected to protrude through the capsule. Although the Nterminal region is highly variable, PspA contains conserved epitopes which elicit antibodies protective against multiple S. pneumoniae serotypes (13,45). CbpA is structurally similar to PspA; the C-terminal choline-binding domains have Ͼ90% amino acid sequence identity, and although there is no sequence similarity, the N-terminal portion of CbpA is also predicted to have a coiled-coil structure (22,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal portion of the choline-binding protein PspA has been predicted to have a coiled-coil structure reminiscent of the M proteins of group A streptococci (46), and this might be expected to protrude through the capsule. Although the Nterminal region is highly variable, PspA contains conserved epitopes which elicit antibodies protective against multiple S. pneumoniae serotypes (13,45). CbpA is structurally similar to PspA; the C-terminal choline-binding domains have Ͼ90% amino acid sequence identity, and although there is no sequence similarity, the N-terminal portion of CbpA is also predicted to have a coiled-coil structure (22,39).…”
Section: Discussionmentioning
confidence: 99%
“…PspA is a member of a family of structurally related choline-binding surface proteins (19,20,46,47); its precise function is uncertain, although it has recently been shown to be capable of binding human lactoferrin (21). Both Ply and PspA are protective immunogens, and mutagenesis of the genes which encode them attenuates virulence of S. pneumoniae (1,3,7,9,10,12,13,31,45). The major pneumococcal autolysin (LytA) is also a choline-binding protein (19,20) which contributes to virulence by mediating the release of Ply and possibly also inflammatory cell wall degradation products (4,9,26).…”
mentioning
confidence: 99%
“…HR108 is a 105-aa (residues 314 to 418) fragment of the ␣-helical domain of PspA/TIGR4, which was shown to contain the most important cross-protective epitopes (29). HR108 is homologous to the region of family 1 PspA/Rx1 to which its major cross-protective epitopes have also been mapped (11,22). The PspA regions homologous to HR108 have been used to classify PspAs into clades and families (18).…”
Section: Vol 71 2003mentioning
confidence: 99%
“…PspA is present on all pneumococcal strains and is serologically variable (15). Mouse models have shown that cross-reactive anti-PspA antisera are also cross-protective (reviewed in references 8,9,60). Human antisera from a phase I vaccine trial were also competent for protecting mice from pneumococcal infection by challenge strains of various PspA types (5a).…”
mentioning
confidence: 99%